Triggering multiple sclerosis at conception and early gestation: The variation in ultraviolet radiation is as important as its intensity - George E. Davis; Matthew J. Davis; Walter E. Lowell (Heliyon, 2023)
Background and objectives: Medical science needs to further elucidate the role of ultraviolet radiation (UVR), geographic latitude, and the role of vitamin D in the autoimmune disease multiple sclerosis (MS). We separated several papers into categories out of the thousands published and used their conclusions to explore the relationship between UVR and MS. Relevance: MS is increasing in incidence, particularly in women where MS is two to three times that in men and particularly severe in African Americans. Methods: We collected UVR data at our observatory in Central Maine and calculated the average coefficient of variation (CVUVR) for each month for 15 years (2007–2021, inclusive). Results: The month of conception (MOC) is more important than the month of birth (MOB) in explaining how UVR triggers the variable genetic predisposition to MS. We hypothesize that the rapidly increasing CVUVR is important in preventing an increase in the activity of the vitamin D receptor (VDR) from August to December, which then requires a higher intensity of UVR later in life to suppress the immune system, therefore predisposing to more MS. Limitations: One observatory at about 44° latitude. Conclusions: While variation in UVR is important at the MOC if UVR exceeds a threshold (e.g., if the sunspot number equals or is greater than 90, usually at a solar cycle MAX, or at elevations above approximately 3,000 feet above sea level), the MS mitigating vitamin D-VDR mechanism is overwhelmed and the genotoxic effects of higher-intensity UVR promote MS in those with a genetic predisposition. What is new in this research: This paper offers a new concept in MS research.